THE PROFILE OF SEXUAL VIOLENCE CASES IN DR SARDJITO HOSPITAL FROM YEAR 2009 TO 2011 - , TAN SZE WEI; , Dr. IBG Surya Putra P.,Sp.F ([Yogyakarta] : Universitas Gadjah Mada, 2014)
BACKGROUND: Sexual abuse is defined as any sexual act or behavior that is imposed on a woman, man, or child, without their consent. High risk populations including the physically or mentally disabled